Becoming the Rolling Quads: Disability Politics at the University of California, Berkeley, in the 1960s. (12th October 2018) - Danforth, Scot
Abstract : Historical analyses of 1960s university campus activism have focused on activities related to the civil rights movement, Free Speech Movement, and opposition to the Vietnam War. This study supplements the historiography of civil disobedience and political activity on college campuses during that tumultuous era with an account of the initiation of the disability rights movement with the Rolling Quads, a group of disabled student activists at the University of California, Berkeley. This small group, with little political experience and limited connections to campus and community activists, organized to combat the paternalistic managerial practices of the university and the California Department of Rehabilitation. Drawing from the philosophy and strategies of the seething political culture of 1969 Berkeley, the Rolling Quads formed an activist cell that expanded within less than a decade into the most influential disability rights organization in the country.